PENGARUH KESADARAN MEREK DAN ASOSIASI MEREK TERHADAP LOYALITAS KONSUMEN PRODUK KOSMETIK WARDAH PADA MAHASISWA DI SURABAYA - Wakika, Cida; Marlena, Novi (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
With brand awareness, many people can easily recognize the brand. In addition to brand awareness, companies need to build relationships with consumers to increase brand recall or what is known as brand associations. The purpose of this study was to analyze the effect of brand awareness and brand associations on consumer loyalty. The type of data used is quantitative data sourced from primary data through distributing questionnaires. The population in this research is 100 respondents. Sampling method using purposive sampling Data were analyzed using multiple linear regression and calculated with IBM SPSS 25. Obtained research shows that there is brand awareness and brand associations that have a significant effect on consumer loyalty, therefore indicating that in increasing consumer loyalty, it will be better if marketing department management increases brand awareness and brand association. Maintaining and increasing good interactions with its customers, the company continues to provide the things that its consumers desire to keep consumers satisfied and remain loyal.